Partial lipodystrophy with nephrotic syndrome. - Hunter, A. M. (BMJ Group, 1978)
A patient with nephrotic syndrome in association with partial lipodystrophy is reported. The features of partial lipodystrophy are well recognized and the renal lesion is a mesangiocapillary glomerulo-nephritis of a dense deposit type with an associated depression of C3. This type of kidney involvement is becoming increasingly recognized as common in the syndrome of partial lipodystrophy.